Formation of Architectural Environment for Blind and Visually Impaired Persons: Problems and Their Solutions - N. A. Lazovskaya; L. V. Agaltsova (Наука и техника, 2004)
The level of accessibility within buildings and urban environments is a manifestation of society’s awareness and acceptance of the needs of people with disabilities. Persons with visual impairment can not only rely on their eye-sight in the case of knowing their whereabouts and reading the information concerned. Architectural and landscape references, road signs, maps and diagrams, color and tactile references may serve as main informative indicators.